Translating academic research into guidance to support healthcare improvement: how should guidance development be reported? - Simon Turner; Charlotte A. Sharp; Jessica Sheringham; Shaun Leamon; Naomi J. Fulop (BMC, 2019)
Abstract Background There is interest internationally in improving the uptake of research evidence to inform health care quality and safety. This article focusses on guidance development from research studies as one method for improving research uptake. While we recognise that implementation strategies on the ´demand´ side for encouraging the uptake of research are important, e.g. knowledge brokers and university-practice collaborations, this article focusses on the ´production´ aspect of how guidance development is reported and the consequent influence this may have on end-users´ receptivity to evidence, in addition to other demand-side processes. Main text The article considers the following question: how is guidance developed and what are the implications for reporting? We address this question by reviewing examples of guidance development reporting from applied health research studies, then describe how we produced guidance for a national study of evidence use in decision-making on adopting innovations. The starting point for reflecting on our experiences is a vignette of the guidance ´launch´ event at a national conference. Conclusions Implications for reporting guidance development and supporting improvement are discussed. These include the need to (a) produce reporting standards for the production of guidance to match reporting standards for other research methods, (b) acknowledge the ´informal´ or emergent aspects of producing guidance and its role within a wider knowledge mobilization strategy, (c) consider guidance development from projects as part of a wider knowledge mobilization strategy, and (d) encourage a receptive environment for guidance development and use, including researcher training, durable funding to support impact, and closer relations between research and practice.